Method of Payment Adoption in Indonesia E-Commerce - Putri, Yolli Eka; Wiryono, Sudarso Kaderi; Nainggolan, Yunieta Anny; Dwi Cahyono, Tomy (The Asian Journal of Technology Management (AJTM), 2019)
Abstract. The emergence of e-commerce nowadays needs a payment method that supports speed and easiness of the transaction. Payment options that are provided by the e-commerce platform influence the customer purchase decision making, but the security of data still becoming an issue for seller and buyer in the e-commerce system. There are popular methods of payment in Indonesian e-commerce, they are transfer, cash on delivery, point of service, virtual account, credit card, and prepaid account. This research aim is to explore the behaviors of Indonesian e-commerce customers based on their ownership and preferred method of payment. This research used a quantitative approach, researchers have surveyed 492 Indonesian e-commerce customer that have shopping experience in e-commerce platforms (website, phone application, etc.). The proposed model in this study has five independent variables from the UTAUT (Unified Theory of Acceptance and Use of Technology) model and its development from other research. The findings of this research are the method of payment that needs less effort to use is used more often in e-commerce transaction, financial benefit is not a factor that attracts an e-commerce customer to have a method of payment, but they very consider fee that is charged because of using a method of payment,  and the higher an account holder perceived security of a method of payment, the higher they keep the account balance.Keywords: E-commerce, payment adoption, payment fee, prepaid payment, UTAUT